- #1

- 90

- 0

I hope I am correct here...

(▲^2 - x▲)(x^3) = ▲^2(x^3) - x▲(x^3)

= ▲▲(x^3) - x( (x+1)^3 - x^3 )

= ▲( (x+1)^3 - x^3 ) - x( (x+1)^3 - x^3 )

= (x+2)^3 - (x + 1)^3 - (x+1)^3 + x^3 )

- x( (x+1)^3 - x^3 )

Is my solution correct?

- Thread starter irony of truth
- Start date

- #1

- 90

- 0

I hope I am correct here...

(▲^2 - x▲)(x^3) = ▲^2(x^3) - x▲(x^3)

= ▲▲(x^3) - x( (x+1)^3 - x^3 )

= ▲( (x+1)^3 - x^3 ) - x( (x+1)^3 - x^3 )

= (x+2)^3 - (x + 1)^3 - (x+1)^3 + x^3 )

- x( (x+1)^3 - x^3 )

Is my solution correct?

- #2

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 956

No. Δ^{2}x^{3} IS Δ(Δ x^{3})= Δ((x+1)^{3}- x^{3})= Δ(3x^{2}+ 3x+ 1)=

3(x+1)^{2}+ 3(x+1)+ 1- (3x^{2}+ 3x+ 1)= 6x+ 6.

3(x+1)

Last edited by a moderator:

- #3

Hurkyl

Staff Emeritus

Science Advisor

Gold Member

- 14,916

- 19

- Last Post

- Replies
- 9

- Views
- 2K

- Replies
- 4

- Views
- 2K

- Last Post

- Replies
- 4

- Views
- 4K

- Last Post

- Replies
- 2

- Views
- 4K

- Last Post

- Replies
- 3

- Views
- 3K

- Last Post

- Replies
- 1

- Views
- 3K

- Last Post

- Replies
- 3

- Views
- 3K

- Last Post

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 0

- Views
- 1K

- Last Post

- Replies
- 5

- Views
- 2K